A comparative study of the combustion properties of normal biogas-air mixture and oxygen-enriched biogas-air (2011)
Research into renewable energy as energy alternatives and decreasing greenhouse gases from organic waste decomposition make biogas a promising alternative for fossil fuel substitution and an energy source from recovery of orga-nic waste in urban, rural and agroindustrial areas. This paper presents a sensitivity analysis of oxygen-enri-ched biogas combustion properties ranging from 22% to 35%. Results showed that properties such as deflagration speed, adiabatic flame temperature, dew temperature and CO2 and H2O percentage increased when oxygen percentage in air was increased. On the other hand, properties such as minimum ignition energy, stoichiometric air volume and dry fume volume decreased when the O2 percentage in air was higher than 21%.